THE UNITED NATIONS COUNCIL’S INTERVENTION IN THE RECONCILIATIAON OF HUMAN RIGHTS AND FUNDAMENTAL FREEDOMS IN NORTH KOREA - Imam Budiman; Muhandis Rajab; Haya Abiyyu; Diani Nurul Yanti; Iqbal Nanda (SEAN Institute, 2023)
Human rights are the basic rights given to mankind by God. They are universal and must be protected, respected and maintained. No one should ignore, reduce or deprive them. Therefore, the implementation of violations of human rights principles is the responsibility of the state as well as the responsibility of mortgage. The United Nations has incorporated respect and appreciation of human rights into the